Development Strategy for Cultural Attractions of the Tulude Traditional Ceremony in the Budo Tourism Village of North Minahasa - Yurike Lewan; Vesty Sambeka; Hendry Kumaat (Jurnal Ragam Pengabdian, 2026)
Culture serves as a social glue that unites individuals within a community, through local wisdom, values and norms are instilled to help regulate individual behavior and ensure harmony within society and provide identity for the community. Budo Village is also known for its traditional ceremonies and traditions that are still preserved today, namely Tulede. The Tulude Traditional Ceremony is a local wisdom of the community that is carried out at the beginning of each new year in January or February. This tradition is a potential cultural tourism for the Budo village community. This tourist attraction has not been developed into a tourist attraction show. The lack of tourism promotion and development of tourist show attraction management into a destination. Sustainable tourism development has a social impact and involves the local community. The purpose of this study is to develop local wisdom of the Tulude traditional ceremony cultural attraction in the Budo Tourism Village, North Minahasa, so as to obtain a model for developing cultural attractions. The method used is a descriptive qualitative method to explain the phenomenon in depth through a qualitative approach that presents descriptive and aims to analyze something related to cultural tourism attractions based on local wisdom in the tourist village and the community. The development strategy for the cultural attraction of the Tulude traditional ceremony is Community Empowerment and Participation, Education and Interpretation, attractive packaging, Development of supporting products for traditional ceremonies, Targeted Marketing and Promotion, Sustainability and Preservation.